(3ejKGb GdfSGAs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce SHMGfg hYR Yf McheI GdChgGe SdWGfg hdGeYHhO ShGg deG fXQJ eYGTQ GdMOhO GdQhMGfjjf HfhQg GdJeGe hfUHfi dOYhJg s
(3BNQgG (B:s
(3hcGf dgf KhGH GdedGFcI GdebQHjf hGdCfHjGA GdeQSdjf hJNdU ef THcI EHdjS GddYjf hGdMeO dehdGfG MeO GdTGcQjf hgh MSHi hfYe GdfUjQ GdeYjf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds